Assessment of dental caries in primary dentition employing caries assessment spectrum and treatment index - Karthik Anchala; Ramasubbareddy Challa; Yamini Vadaganadham; Rekhalakshmi Kamatham; Vemula Deepak; Sivakumar Nuvvula (Wolters Kluwer Medknow Publications, 2016)
Background: Caries assessment spectrum and treatment (CAST) index was developed as an innovative instrument for evaluating dental caries in epidemiological studies. Aim: The aim of the study was to assess the usefulness of CAST in evaluating caries prevalence and treatment needs among children in primary dentition stage. Materials and Methods: Children in the age range of 5-6 years were selected and their caries status, along with the treatment needs, was recorded using CAST index. The differences in caries status between maxillary and mandibular arches, right and left quadrants as well as boys and girls were assessed using Mann-Whitney U test with the level of significance set at 0.05 and correlation of the distribution of CAST codes among the evaluated teeth was explored through Spearman's rank correlation coefficient. Results: A strong correlation was found between the status of the teeth from the right and left sides of the oral cavity. The correlation coefficient (r) for neighboring maxillary anteriors was 0.67 and 0.57, whereas 1 for all mandibular anteriors (P < 0.001). The correlation coefficient (r) for neighboring maxillary posteriors was <0.3, whereas it was 0.48 and 0.18 for mandibular posteriors (P < 0.001). Correlations were found to be weak (r 0.07-0.29) between maxillary and mandibular arches. Conclusions: In the evaluated population, the strongest correlation was found for the distribution of caries stages in primary incisors as well as molars on the right side of the mouth and the percentage of molars with carious lesions was especially high for second primary molars.